2018
DOI: 10.1093/neuonc/noy145
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the immune microenvironment of diffuse intrinsic pontine glioma: implications for development of immunotherapy

Abstract: DIPG tumors have neither a highly immunosuppressive nor inflammatory microenvironment. Therefore, major considerations for the development of immunotherapy will be the recruitment, activation, and retention of tumor-specific effector immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 39 publications
7
142
2
Order By: Relevance
“…In line with these findings, Lieberman et al show that in contrast to pediatric high-grade and low-grade glioma, DIPG tissue does not show enhanced T cell infiltration compared to adjacent non-tumor tissue. In addition, no increase in chemokines and inflammatory cytokines was observed (106). Collectively, these findings demonstrate minimal immune activation in the DIPG microenvironment in contrast to other types of brain tumors.…”
Section: Dipg Displays a Unique Immune Environment With Minimal Immunmentioning
confidence: 58%
“…In line with these findings, Lieberman et al show that in contrast to pediatric high-grade and low-grade glioma, DIPG tissue does not show enhanced T cell infiltration compared to adjacent non-tumor tissue. In addition, no increase in chemokines and inflammatory cytokines was observed (106). Collectively, these findings demonstrate minimal immune activation in the DIPG microenvironment in contrast to other types of brain tumors.…”
Section: Dipg Displays a Unique Immune Environment With Minimal Immunmentioning
confidence: 58%
“…Glioblastoma (GBM) is the most frequent and the highest malignant glioma (grade IV), it usually causes significant mortality and morbidity, and it has a 5‐year overall survival (OS) of no > 5% . In the past few decades, the treatment of glioma has made great progress and development, including surgical resection, radiotherapy, chemotherapy, immunotherapy, and molecular targeted therapy . However, the prognosis of glioma remains poor, especially for GBM.…”
mentioning
confidence: 99%
“…GBM tumors establish an immunosuppressive environment by the release of immunosuppressive cytokines, such as TGF-β and IL-10, by the recruitment or induction of immunosuppressive cells, such as regulatory T cells, myeloid-derived suppressor cells, or tumor associated macrophages, and by the expression of immune checkpoint receptor ligands (47)(48)(49)(50)(51)(52)(53). In comparison to adult GBM, initial studies of the tumor microenvironment in DIPG have found that there is a low number of immune infiltrates in human DIPG tumors and that they do not express inflammatory cytokines and chemokines (54,55). These data provide support for the use of an immune modulatory therapeutic strategy to enhance the recruitment of immune cells into the tumor, with the aim of mounting an effective anti-DIPG immune response.…”
Section: Discussionmentioning
confidence: 99%